Un recorrido por el taller - Tesone, Pablo (2017)
Frequently, communication in public spaces is related with signage, defined by Joan Costa (2007) as the action and effect of placing signals in the public environment. In the course of my performance as a teacher in the field, this vision has changed and become more complex with the incorporation of new contents and ways of approaching them. This writing is an attempt to reflect those modifications from my experience in Taller de Diseño en Comunicación Visual 4A.